People and biodiversity policies : impacts, issues, and strategies for policy action - 460187 Bagnoli, Phillip; Goeschl, Timo; Kovacs, Ferenc; Organisation for Economic Co-operation and Development (London, UK : OECD, 2008)
Includes bibliographical references (p. 225-243)